Process variables in organizational stress management intervention evaluation research: a systematic review - Bo M Havermans; Roosmarijn MC Schelvis; Cécile RL Boot; Evelien PM Brouwers; Johannes R Anema; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: This systematic review aimed to explore which process variables are used in stress management intervention (SMI) evaluation research. METHODS: A systematic review was conducted using seven electronic databases. Studies were included if they reported on an SMI aimed at primary or secondary stress prevention, were directed at paid employees, and reported process data. Two independent researchers checked all records and selected the articles for inclusion. Nielsen and Randall's model for process evaluation was used to cluster the process variables. The three main clusters were context, intervention, and mental models. RESULTS: In the 44 articles included, 47 process variables were found, clustered into three main categories: context (two variables), intervention (31 variables), and mental models (14 variables). Half of the articles contained no reference to process evaluation literature. The collection of process evaluation data mostly took place after the intervention and at the level of the employee. CONCLUSIONS: The findings suggest that there is great heterogeneity in methods and process variables used in process evaluations of SMI. This, together with the lack of use of a standardized framework for evaluation, hinders the advancement of process evaluation theory development.